2018
DOI: 10.31223/osf.io/jdqku
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-dependent compaction as a mechanism for regular stick-slips

Abstract: Owing to their destructive potential, earthquakes receive considerable attention from laboratory studies. In friction experiments, stick-slips are studied as the laboratory equivalent of natural earthquakes, and numerous attempts have been made to simulate stick-slips numerically using the discrete element method (DEM). However, while laboratory stick-slips commonly exhibit regular stress drops and recurrence times, stick-slips generated in DEM simulations are highly irregular. This discrepancy highlights a ga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, when acting in concert with a time‐dependent strengthening mechanism (such as compaction by pressure solution creep), granular flow causes slip‐dependent dilatation that counteracts the strengthening resulting from time‐dependent compaction. Hence, the interplay between dilatant granular flow and one or more compaction mechanisms gives rise to velocity‐weakening behavior, depending on the relative rates of dilatation and compaction (see van den Ende & Niemeijer, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…However, when acting in concert with a time‐dependent strengthening mechanism (such as compaction by pressure solution creep), granular flow causes slip‐dependent dilatation that counteracts the strengthening resulting from time‐dependent compaction. Hence, the interplay between dilatant granular flow and one or more compaction mechanisms gives rise to velocity‐weakening behavior, depending on the relative rates of dilatation and compaction (see van den Ende & Niemeijer, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…(Abed Zadeh et al, 2019) showed experimentally that similar transitions can be achieved by varying the imposed sliding velocity and the stiffness of their apparatus. Furthermore, we have not explicitly considered time-dependent physicochemical processes that have been shown to influence the frictional behavior of granular aggregates in discrete element method simulations (van den Ende & Niemeijer, 2018). However, such processes are likely very slow under the conditions that our experiments were performed at (Rossi et al, 2007).…”
Section: System Physicsmentioning
confidence: 99%
“…The intermittent style of deformation that such artificial systems exhibit has striking similarities with natural seismicity, such as power-law scaling of event sizes and Omori-type correlations in the time domain. Characteristic events or G-R type behavior can be reproduced by Burridge-Knopoff type spring-block models (Brown et al, 1991;Carlson & Langer, 1989), Lattice-Boltzmann models (Benzi et al, 2016), cellular automata and rupture mechanics models (e.g., Ben-Zion & Rice, 1993Dahmen et al, 1998;Klein et al, 2017), discrete element method simulations (e.g., Ferdowsi et al, 2013;van den Ende & Niemeijer, 2018), and laboratory experiments (e.g., Anthony & Marone, 2005;Baró et al, 2013;Dalton & Corcoran, 2001Hamilton & McCloskey, 1997;Hayman et al, 2011;Johnson et al, 2013;Mair et al, 2002;Jiang et al, 2017).…”
mentioning
confidence: 99%
“…Dorostkar and Carmeliet used the coupled discrete element and computational fluid dynamics methods to study the stick–slip characteristics of a shear grain fault gouge and compared the stick–slip event characteristics of a fault gouge under wetting and nonwetting conditions. van de Ende and Niemeijer used a numerical simulation of the external force mode with a dynamic change in pressure over time to provide an explanation for the regular stress drop and intermittent sliding deformation manifested in laboratory stick–slip. Li et al used the step function of the time-varying initial damage to qualitatively describe the stick–slip deformation of shear bands caused by the formation of microcracks at different times during the cracking process of brittle rock, and they obtained the internal reasons for the stress drop caused by shear fracture and frictional stick–slip.…”
Section: Introductionmentioning
confidence: 99%